Dosimetric divergence in ICBT vs. IC/ISBT configurations: Comparative analysis of three optimization algorithms for cervical cancer brachytherapy - Chen, Jihong; Hong, Jiabiao; Chen, Kaiqiang; Zhang, Xiuchun; Wang, Guohua; Bai, Penggang (PLOS ONE, 2025)
Objective To compare dosimetric differences among graphical-based manual planning (MA), simulated annealing inverse optimization (IPSA), and hybrid inverse optimization (HIPO) for cervical cancer in both intra-cavitary brachytherapy (ICBT) and interstitial brachytherapy combined with ICBT (IC/ISBT) settings, providing evidence for clinical optimization method selection. Methods This study consisted of 60 cervical cancer patients undergoing CT-guided three-dimensional brachytherapy, including 30 ICBT patients and 30 IC/ISBT patients. Plans were generated using MA, IPSA, and HIPO. The dosimetric parameters for the high-risk clinical target volume (HRCTV) including D100%, V150%, V200%, conformity index (CI), homogeneity index (HI) were compared. Meanwhile, the dosimetric parameters D1cc, D2cc for the bladder, rectum, sigmoid, and total treatment time were evaluated. Results Compared with MA, both IPSA and HIPO delivered lower doses to organs at risk (OARs). The total treatment time was significantly shorter for HIPO compared to IPSA and MA (P < 0.05). In ICBT patients, the D1cc and D2cc of OARs were lower for IPSA compared to HIPO (P > 0.05), while the CI was significantly better for HIPO (P < 0.05). Nevertheless, in IC/ISBT patients, D2cc of rectum for HIPO was significantly lower compared to IPSA (P < 0.05), with better CI. Conclusion Inverse optimization effectively reduces doses to OARs while maintaining target coverage. HIPO appears to be the preferred choice for IC/ISBT, due to shortened treatment time, superior CI and rectal protection compared with IPSA.